(untitled) (Revista Cercurilor studenţeşti ale Departamentului de Limba şi Literatura Franceză, 2024)
Reading is a true indicator of the social history of literary reception, with great heuristic value. The evolution of the female act of reading translates the evolution of the practices which found the emancipation of a whole social category, but also the evolution of the relationship of a person to herself, therefore the access of the individual to his interiority through the paradoxical discovery of otherness. This article will study the different stages of the transformation of the female reading gesture over the centuries, with the aim of showing how the historical-cultural reorganization – represented by the two waves of female literacy and the important social movements of the 18th century – has fundamentally influenced the reading practices and the reception activity. It will also insist, thanks to a case study, on the transsubjective valences associated with the act of reading, which allow the conversion to oneself of the individual by the readjustment of the initial socio-cultural capital and the access to a form of transpersonal truth, a self-reflective approach that combines reading and playing.